Management of low-risk early-stage cervical cancer: Should conization, simple trachelectomy, or simple hysterectomy replace radical surgery as the new standard of care? - Ramirez, Pedro T. (Gynecol Oncol, 2013)
The standard treatment for women with early-stage cervical cancer (IA2-IB1) remains radical hysterectomy with pelvic lymphadenectomy. In select patients interested in future fertility, the option of radical trachelectomy with pelvic lymphadenectomy is also considered a viable option. The possibility of less radical surgery may be appropriate not only for patients desiring to preserve fertility but also for all patients with low-risk early-stage cervical cancer. Recently, a number of studies have explored less radical surgical options for early-stage cervical cancer, including simple hysterectomy, simple trachelectomy, and cervical conization with or without sentinel lymph node biopsy and pelvic lymph node dissection. Such options may be available for patients with low-risk early-stage cervical cancer. Criteria that define this low-risk group include: squamous carcinoma, adenocarcinoma, or adenosquamous carcinoma, tumor size <2 cm, stromal invasion <10mm, and no lymph-vascular space invasion. In this report, we provide a review of the existing literature on the conservative management of cervical cancer and describe ongoing multi-institutional trials evaluating the role of conservative surgery in selected patients with early-stage cervical cancer.